Příklady z matematiky

Každé načítání stránky vám zadá nové příklady !




Jméno:_____________________________
 
X + Y - Z = 26
Z + Y + X = 120
Z + X - Y = 42

X=
Y=
Z=






X + Y - Z = 52
Z + Y + X = 108
Z + X - Y = 48

X=
Y=
Z=






X + Y - Z = -37
Z + Y + X = 63
Z + X - Y = 49

X=
Y=
Z=






X + Y - Z = 2
Z + Y + X = 92
Z + X - Y = 64

X=
Y=
Z=






X + Y - Z = 35
Z + Y + X = 81
Z + X - Y = -15

X=
Y=
Z=






X + Y - Z = 53
Z + Y + X = 79
Z + X - Y = 31

X=
Y=
Z=






X + Y - Z = 18
Z + Y + X = 32
Z + X - Y = -4

X=
Y=
Z=






X + Y - Z = 16
Z + Y + X = 94
Z + X - Y = 36

X=
Y=
Z=






X + Y - Z = 25
Z + Y + X = 31
Z + X - Y = -19

X=
Y=
Z=